2018
DOI: 10.1080/09853111.2018.1427407
|View full text |Cite
|
Sign up to set email alerts
|

Paleozoic subduction of the southern Dunhuang Orogenic Belt, northwest China: metamorphism and geochronology of the Shuixiakou area

Abstract: Amphibolites in the Shuixiakou area of the southern Dunhuang Orogenic Belt, southernmost Central Asian Orogenic Belt (CAOB), occur as lenses within hornblende-biotite-plagioclase gneiss or pelitic schist, exhibiting block-in-matrix feature of tectonic mélange. Three generations of metamorphic mineral assemblages (M1, M2, and M3) have been recognized in the garnetbearing amphibolite lenses. The metamorphic prograde assemblage (M1) is documented with inclusion trails (hornblende + plagioclase + quartz) within ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…1B). The latest studies have confirmed that the Dunhuang terrane is constituted by the Precambrian Dunhuang Complex (Zhang et al, 2013;Zong et al, 2013;Zhao et al, 2013Zhao et al, , 2015aZhao et al, , 2015bZhao et al, , 2017Wang et al, 2013b;Zhao and Sun, 2018) and a Paleozoic magmatic-metamorphic complex (Zong et al, 2012;He et al, 2014;Zhao et al, 2015cZhao et al, , 2016Zhao et al, , 2017Wang et al, 2016aWang et al, , 2016bWang et al, , 2016cWang et al, , 2017aWang et al, , 2017bWang et al, , 2017dWang et al, , 2018. It is now considered to be a mobile belt that underwent intensive reworking during a Paleozoic orogeny (Zhao et al, 2016;Wang et al, 2016aWang et al, , 2017aWang et al, , 2017bShi et al, 2018).…”
Section: Geological Backgroundmentioning
confidence: 98%
See 2 more Smart Citations
“…1B). The latest studies have confirmed that the Dunhuang terrane is constituted by the Precambrian Dunhuang Complex (Zhang et al, 2013;Zong et al, 2013;Zhao et al, 2013Zhao et al, , 2015aZhao et al, , 2015bZhao et al, , 2017Wang et al, 2013b;Zhao and Sun, 2018) and a Paleozoic magmatic-metamorphic complex (Zong et al, 2012;He et al, 2014;Zhao et al, 2015cZhao et al, , 2016Zhao et al, , 2017Wang et al, 2016aWang et al, , 2016bWang et al, , 2016cWang et al, , 2017aWang et al, , 2017bWang et al, , 2017dWang et al, , 2018. It is now considered to be a mobile belt that underwent intensive reworking during a Paleozoic orogeny (Zhao et al, 2016;Wang et al, 2016aWang et al, , 2017aWang et al, , 2017bShi et al, 2018).…”
Section: Geological Backgroundmentioning
confidence: 98%
“…440-360 Ma arc-related granitoids (Wang et al, 2016b(Wang et al, , 2016cZhao et al, 2017), (garnet-bearing) amphibolite/highpressure mafic granulite with a metamorphic age of ca. 440-350 Ma (Zong et al, 2012;He et al, 2014;Zhao et al, 2016;Wang et al, 2016aWang et al, , 2017aWang et al, , 2017bWang et al, , 2017dWang et al, , 2018, and ca. 335-315 Ma postcollisional potassic granites (Zhao et al, 2017).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). The Dunhuang region, as a Palaeozoic orogenic belt and part of the CAOB, represents a vital component of the southernmost CAOB within the Tianshan-Beishan-Mongolia-Xing'anling orogen (Yue et al 2001;Xiao et al 2010;Zhao et al 2016;Wang et al 2018;Zhu et al 2019). Meanwhile, the Beishan orogenic belt located to the north side of the Dunhuang region is also a part of the southernmost CAOB.…”
Section: Geological Background and Samplingmentioning
confidence: 99%
“…In the southern Dunhuang Block, many eclogite, granulite, and amphibolite are exposing in the Hongliuxia complex. They record the Silurian–Devonian “clockwise” metamorphism P–T–t paths (Wang et al, 2017; Wang et al, 2018; Wang, Chen, et al, 2017). They are mainly exposed as tectonic blocks within the metasedimentary rocks (metamorphosed trench turbidites), exhibiting the “block‐in‐matrix” fabric (Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%